2018
DOI: 10.1002/ecs2.2439
|View full text |Cite
|
Sign up to set email alerts
|

Context‐dependent mutualisms in the Joshua tree–yucca moth system shift along a climate gradient

Abstract: Changing climate patterns can affect the geographic distribution of species through effects on species interactions. Iconic Joshua trees are limited to a narrow range of climate conditions, and climate change is expected to shift suitable habitat to higher elevations and latitudes than their current geographic distribution. As such, the survival of the species requires colonization of new habitats. However, Joshua trees form an obligate mutualistic relationship with yucca moths that pollinate the flowers but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 66 publications
1
28
1
Order By: Relevance
“…These aspects of species biology are not necessarily congruent; for example, patterns of success such as fruit production do not necessarily align with geographic patterns of demographic metrics for Joshua trees. Recent research into pollination ecology has shown a peak in pollination (by the obligate pollinator, the yucca moth; Pellmyr and Segraves 2003) and fruit set in areas on the lower end of the area of refugia generally identified here (Harrower and Gilbert 2018). This is consistent with other findings that have shown that higher temperatures across a geographic gradient positively affected fruit set due to moth activity, whereas patterns in tree density showed the opposite pattern (St. Clair and Hoines 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These aspects of species biology are not necessarily congruent; for example, patterns of success such as fruit production do not necessarily align with geographic patterns of demographic metrics for Joshua trees. Recent research into pollination ecology has shown a peak in pollination (by the obligate pollinator, the yucca moth; Pellmyr and Segraves 2003) and fruit set in areas on the lower end of the area of refugia generally identified here (Harrower and Gilbert 2018). This is consistent with other findings that have shown that higher temperatures across a geographic gradient positively affected fruit set due to moth activity, whereas patterns in tree density showed the opposite pattern (St. Clair and Hoines 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Following on that study, Barrows and Murphy-Mariscal (2012), using a finer scale, a more restricted extent focusing on populations of the western Joshua tree, and a uniform maximum temperature increase of 3°C, predicted persistence of JTNP Joshua trees, but within an area that was just 10% of their current distribution. Others have examined key components of Joshua tree demography, such as survivorship following fires, juvenile growth, pollination, fruit production, and seed predation, all within a climate change context (DeFalco et al 2010, Esque et al 2015, Borchert and DeFalco 2016, Harrower and Gilbert 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Second, they can change the environmental context of the interaction -such as when tracking one environmental variable results in a change in a second -and alter the outcome of specific interactions (Bronstein 1994;Davis et al 1998a;Tylianakis et al 2008;Chamberlain et al 2014;Harrower and Gilbert 2018). The results we have presented here provide an example of the latter and point to the importance of quantifying interspecific interactions under different environments in order to better predict responses to climate change.…”
Section: A Role For Biotic Interactions In Range-shifts Associated Wimentioning
confidence: 81%
“…Y. brevifolia has a discontinuous distribution in the Mojave Desert, with highest population density on well-drained alluvial fans adjacent to desert mountain ranges ( Cole et al, 2011 ). Because of this narrow range of abiotic climate conditions, Y. brevifolia populations have been shifting to higher elevations with climate change ( Harrower and Gilbert, 2018 ). Indeed, the elevated temperatures consequent to climate change result in shorter frost seasons, and thus, seasonal water availability, causing the reduction and range shift of Y. brevifolia populations ( Archer and Predick, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increase in fires in the northern range could further limit Y. brevifolia ’s expansion there, as a study at the southern range found that increased fires due to prolonged droughts increased mortality of Y. brevifolia , especially in the younger individuals ( Defalco et al, 2010 ). Finally, the distribution of the mutualistic yucca moths ( Tegeticula synthetica and Tegeticula antithetica ) must match the expansion into refugia regions ( Sweet et al, 2019 ), which is dependent on the elevation gradient ( Harrower and Gilbert, 2018 ). A finer scale study, focused on the southern range of Y. brevifolia found that under a 3°C temperature increase scenario, 90% of the present distribution would be reduced ( Barrows and Murphy-Mariscal, 2012 ).…”
Section: Introductionmentioning
confidence: 99%